THE IMPLEMENTATION OF READ-ALOUD DESCRIPTIVE TEXT IN TEACHING ENGLISH SPEAKING TO JUNIOR HIGH SCHOOL STUDENTS - Meli Agustina; Jauhar Helmie; Halimah (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2026)
This research aims to investigate the implementation of the read-aloud method in teaching English speaking to Grade VII students involved 27 with 13 males and 14 females at SMPN 3 Cianjur and to identify the difficulties encountered during the process. The data analysis employed a descriptive qualitative approach, with data collected through classroom observations, questionnaires, and teacher interviews. The findings revealed that the read-aloud method was applied through several stages: teacher modeling, guided student reading, individual and pair practice, and oral description tasks. This technique helped improve students’ pronunciation, intonation, fluency, and speaking confidence. Most students responded positively to the method, stating that it made them more accustomed to speaking English in front of others and reduced their fear of making mistakes. Although there were some difficulties found by teacher and students, this technique is advised to be used in teaching speaking. The teacher also faced difficulties in managing students with different levels of English proficiency and in maintaining student motivation.